Pengaruh Penanaman Modal dalam Negeri, Penanaman Modal Asing dan Penyerapan Tenaga Kerja terhadap Jumlah Penduduk Miskin pada Kabupaten/Kota di Sumatera Utara - Yani, Ayu Syah Fitri; Lubis, Irsad (IPM2KPE, 2025)
This study aims to analyze the effect of domestic investment (PMDN), foreign investment (PMA), and labor absorption (PTK) on the number of poor people (JM) in 33 districts/cities in North Sumatra Province during the period 2016-2022. The data used are panel data obtained from the Central Statistics Agency (BPS), the Investment and One-Stop Integrated Service Office (DPMPTSP), and the Investment Coordinating Board (BKPM). The analysis model used in this study is the Fixed Effect Model, as determined through the Chow test and the Hausman test. The results of the study indicate that PMDN and PTK have a negative and significant effect on the number of poor people, while PMA does not have a significant effect. With an Adjusted R-Squared value of 99.37%, it can be concluded that the variation in the number of poor people is predominantly influenced by these three variables. The government is expected to continue to encourage domestic investment and job creation as the main strategy in poverty alleviation in North Sumatra. Keywords: Domestic Investment, Foreign Investment, Labor Absorption, Number of Poor People